The Italian Experience at its Periphery: Change and Continuity in the Psychiatric Hospitals of Teramo - Piergiorgio Di Giminiani (Opticon1826, 2009)
Franco Basaglia holds a special place in the memory of all psychiatric workers in Italy. Nonetheless, recollections of the radical and successful experiment of Trieste, the Northern town where Democratic Psychiatric was born, strikingly differ from the history of deinstitutionalization in other areas of Italy. This paper will explore how the Basaglian model, which implied a radical restructuring of Italian society, was articulated in localized domains, especially in relation to the restructuring of the social function of psychiatry.
Keywords: Democratic Psychiatric